Integration of TQM in blended learning / Noraida Haji Ali … [et al.] - Yacob, Azliza; Mohd Saman, Md Yazid; Yusoff, Mohd Hafiz (UiTM Press, 2016)
Many tools have been developed to assist the teaching and learning process. However, it is difficult to find one suitable for all students’ needs. With strong support from the top management, TQM can be applied to higher education which can provide better service. Blended learning, which includes student-centered and independent learning approaches, requires a strong sense of motivation. Although motivation is an important factor in blended learning, the literature has not adequately explored how students can be motivated in blended learning. The integration of TQM in Blended Learning using PDCA will ensure more efficient learning. 99 students, who took Computer Programming in Universiti Malaysia Terengganu were involved in this research. This study proposed the use of the TQM approach in the implementation of Blended Learning. Using this approach, the element of Plan and Do was used in the preparatory work. For face- to-face learning, the Check element was implemented, while the Action element was found to be very useful for enrichment work. The result of the study found that the total mean score after intervention was 18.49 higher than before the intervention showing that TQM integration in Blended Learning enhances student learning performance. This paper contributes to the motivation to apply TQM to learning using a web-based environment and face-to-face mode.